2022
DOI: 10.3389/fimmu.2022.1029006
|View full text |Cite
|
Sign up to set email alerts
|

Low perforin expression in CD8+ T lymphocytes during the acute phase of severe SARS-CoV-2 infection predicts long COVID

Abstract: T cell cytotoxicity plays a major role in antiviral immunity. Anti-SARS-CoV-2 immunity may determine acute disease severity, but also the potential persistence of symptoms (long COVID). We therefore measured the expression of perforin, a cytotoxic mediator, in T cells of patients recently hospitalized for SARS-CoV-2 infection. We recruited 54 volunteers confirmed as being SARS-CoV-2-infected by RT-PCR and admitted to Intensive Care Units (ICUs) or non-ICU, and 29 age- and sex-matched healthy controls (HCs). Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Further studies may look deeper into the early phase of the disease, including more extensive analyses of anti-SARS-CoV-2 humoral and adaptive T-cell specific responses, and its consequence on long term. Thus, a recent study suggested low perforin expression in CD8 + T cells during the acute phase is associated the persistence of symptoms 120 . Also, once our cohort is mainly constituted by hospitalised patients, it would be ideal to have enlarged our sample to include more patients who never required hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies may look deeper into the early phase of the disease, including more extensive analyses of anti-SARS-CoV-2 humoral and adaptive T-cell specific responses, and its consequence on long term. Thus, a recent study suggested low perforin expression in CD8 + T cells during the acute phase is associated the persistence of symptoms 120 . Also, once our cohort is mainly constituted by hospitalised patients, it would be ideal to have enlarged our sample to include more patients who never required hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…When we examined NK cell natural cytotoxicity (NC) and ADCC function in MIS-C, we found that NK cells in MIS-C had decreased degranulation and cytokine production in NC and ADCC. Furthermore, NK cells in children with MIS-C had decreased perforin; this is likely attributed to NK cell training, as opposed to a primary perforin defect based on previous studies in severe COVID-19 in adults (Kundura et al, 2024). One hypothesis for why the NK cells may be hypofunctional was that the pro-inflammatory milieu drove them to exhaustion.…”
Section: Discussionmentioning
confidence: 89%
“…This suggests that either cytotoxic T cell responses to SARS-CoV-2 are either inhibited in patients of advanced age or that older patients already have a higher baseline level of cytotoxic CD8+ T cells pre-infection, the latter explanation being the most consistent with previous studies. Additionally, several studies have demonstrated the increased presence of cytotoxic T cells in severe COVID-19, and recent studies suggest that the cytotoxic T cell response may be associated with the persistence of COVID-19 symptoms after the acute phase of infection (95)(96)(97). Given the important role of cytotoxic T cells in killing virus-infected cells and their potential to cause endothelial damage (97), further studies examining the functions of cytotoxic T cells in severe COVID-19 patients of all ages are prudent.…”
Section: Discussionmentioning
confidence: 99%